Development of instant phirni mix (a traditional dairy dessert) from high amylose rice, skim milk powder and carboxymethyl cellulose-resistant starch, predicted glycemic index and stability during storage. (August 2021) - Naseer, Bazila; Naik, H.R.; Hussain, Syed Zameer; Bhat, Tashooq; Nazir, Nageena
Abstract: High amylose rice (HAR) and carboxymethyl cellulose (CMC) are ideal choices to enhance the resistant starch and reduce the glycemic index of dairy desserts. Therefore, the effect of ingredient composition (i.e., skim milk powder: high amylose rice flour -SMP: HAR, and carboxymethyl cellulose- CMC) on physical characteristics of phirni dry mix were investigated in the present study. Variation in SMP: HAR flour and CMC concentration significantly (p < 0.05) affected the insolubility index, wettability, Hausner ratio, luminosity (L*), and yellowness (b*) of different phirni dry mix samples. Design expert predicted SMP (70%), HAR (30%) and CMC concentration of 0.85% as desirable conditions for preparation of phirni dry mix. A typical A-type diffraction pattern and absorption bands representative of proteins, lactose and starch were detected in optimized phirni dry-mix (OPDM). Irrespective of packaging material and storage condition, resistant starch (RS) increased significantly (p < 0.05) while predicted glycemic index (pGI) showed significant (p < 0.05) decrease during storage. However, maximum RS content (7.57%) and minimum pGI (44.95) were recorded in LDPE packed samples (LDPE-PS) on 90th day of storage under accelerated conditions. At the same time, moisture content, water activity, free fatty acids, and peroxide value increased significantly (p < 0.05), while overall acceptability showed a significant (p < 0.05) decrease in LDPE-PS. The inference drawn from the present study was that irrespective of packaging material and storage condition, the OPDM was safe to consume up to 90 days, however, aluminum laminated package and ambient storage condition could be better options to retain the quality of OPDM with better consumer acceptability. Highlights: High amylose rice and carboxymethyl cellulose were explored for development of instant dairy dessert ( phirni) . X-ray diffraction results showed a typical A-type diffraction pattern in developed dairy mix. Phirni mix was found shelf stable up to 3 months under ambient and accelerated conditions. Resistant starch was increased while predicted glycemic index decreased during storage. Based on the results of the study, the developed dairy mix was categorized as low glycemic index food.